A framework for stakeholder engagement and sustainable development in MNCs. Issue 1 (6th May 2014) - Rhodes, Jo; Bergstrom, Bruce; Lok, Peter; Cheng, Vincent
Abstract : Purpose: – The aim of this study is to determine key factors and processes for multinational companies (MNCs) to develop an effective stakeholder engagement and sustainable development (SD) framework. Design/methodology/approach: – A qualitative multiple-case approach was used. A triangulation method was adopted (interviews, archival documents and observations) to collect data on three global firms (MNCs). Nine senior executives were interviewed for this study (three from each firm). An initial literature review was conducted to explore possible practices and factors (the deductive approach) to SD. Interview data were analysed using Nvivo to obtain appropriate nodes and themes for the framework. A comparison of findings from interview data, archival data, factors, themes and cross cases comparison were used to develop the final conceptual framework (the inductive approach). Findings: – The results suggested that stakeholder engagement is a key mediator between "stakeholder network" (internal and external factors) and outcomes (corporate social responsibility, social capital, shared value and SD). Key internal factors such as human capital/talent, technology, culture, leadership and processes such as collaboration, knowledge sharing and co-creation of value with stakeholders were identified. These internal factors and processes must be integrated and aligned with external factors such as social, political, cultural, environment and NGOs to achieve effective stakeholder engagement. Originality/value: – This study has captured the insight of how MNCs developed their SD strategies. Accessing internal data from MNCs is always a challenge and in-depth qualitative approach is warranted here to obtain underlying strategies, processes and meaning to SD in MNCs.